EFFECTIVENESS GUIDANCE SERVICES GROUP TO IMPROVE STUDENT LEARNING CONCEPTS SMP NEGERI 1 EAST ANGKOLA - Fitri Yuniza (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study was based on issues found in research are: 1) Some students are less earnest in learning. 2) During school hours lasted most students roam outdoors. 3) Some students come to school not only to learn but only to seek sensation. 4) Some students often come to school just to show the style of dress it with violating regulations specify in school. 5) Often late also things that are usual for most students with a variety of reasons that are not clear. The formulation of the problem in this study as follows: 1) How to increase students' concept of SMP Negeri 1 Angkola East before and after tutoring services group in the experimental group? 2) How to increase students 'concept of SMP Negeri 1 Angkola East in the control group, purpose of this research are: 1) To determine the increase students' concept of SMP Negeri 1 Angkola East before and after tutoring services group in the experimental group. 2) To determine the increase students' concept of SMP Negeri 1 Angkola East in the control group. Where the research was conducted in SMP Negeri 1 Angkola East. The population in this study were 200 students, the samples were used as the experimental group is class VII-1 as many as 10 students, while samples were used as a control group is a class VII-4 as many as 10 students, so that the entire sample was 20 students. Researchers provide guidance services group meetings 5 times. The method used is the method Experimental Desaign True. Revealer tool data used in this research is to use a questionnaire. Data were analyzed using SPSS version 20 using the formula Wilcoxon signed rank test and test one sample kolmogorovsmirnop test. The results of research in the can researcher in the experimental group which originally totaled 73.54 into 94.34, while the control group was originally totaled 62.57 into 75.94. The conclusion of this study is the group counseling services are very effective in improving student learning concepts in the experimental group that is class VII-1 SMP Negeri 1 Angkola East.